Defluoridation of water using as-synthesized Zn/Al/Cl anionic clay adsorbent: equilibrium and regeneration studies - Mandal, Sujata; Mayadevi, S. (Journal of Hazardous Materials, 2009)
Zn/Al/Cl anionic clay has been synthesized by co-precipitation method and applied for adsorption of fluoride in aqueous medium. Equilibrium adsorption data were fitted to Langmuir, Freundlich, Temkin, and Generalized isotherm equations. Thermodynamic parameters like Delta G and Delta H values show the feasibility and exothermic nature of the adsorption process. Influence of solution pH and presence of other anions on fluoride adsorption by the clay has also been studied. Presence of carbonate in water was found to have an adverse effect on fluoride adsorption by the clay. pH(pzc) of the clay has been found to be 8.97. A two-step 1st order kinetic model was used to explain the fluoride adsorption kinetics of the as-synthesized clay. It was possible to regenerate the adsorbent with an aqueous solution of 0.01 M NaOH and the effect of regeneration on fluoride adsorption was reported up to five regeneration cycles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Isotherm; kinetics; Regeneration